Metabolic profiling of Vitex Pubescens Vahl bark via UPLC-ESI-QTOF/MS/MS analysis and evaluation of its antioxidant and acetylcholinesterase inhibitory activities - Safa Abdelbaset; Iriny M. Ayoub; Osama G. Mohamed; Ashootosh Tripathi; Omayma A. Eldahshan; Dina M. El-Kersh (BMC, 2024)
Abstract Background Alzheimer's disease is a neurodegenerative age-related disease that primarily affects the elderly population leading to progressive memory impairments and neural deficits. It is counted as a major cause of geriatric dependency and disability. The pathogenesis of Alzheimer's disease incidence is complex and involves various hypotheses, including the cholinergic hypothesis, deposition of β-amyloid plaques, neuroinflammation, oxidative stress, and apoptosis. Conventional treatments such as donepezil aim to delay the symptoms but do not affect the progression of the disease and may cause serious side effects like hepatoxicity. The use of natural candidates for Alzheimer's disease treatment has drawn the attention of many researchers as it offers a multitargeted approach. Methods This current study investigates the metabolic profiles of total defatted methanolic extract of Vitex pubescens bark and its polar fractions, viz. ethyl acetate and n-butanol, using ultra-performance liquid chromatography-electrospray ionization-quadrupole time-of-flight tandem mass spectrometry(UPLC-ESI-QTOF/MS/MS) technique as well as evaluate the antioxidant using free radical scavenging assays, viz. DPPH and ABTS assays and in-vitro acetylcholinesterase inhibitory activities using Ellman's microplate assay. Results Metabolic profiling revealed a total of 71, 43, and 55 metabolites tentatively identified in the defatted methanolic extract, ethyl acetate, and n-butanol fractions, respectively. Phenolic acids were the most abundant class, viz. benzoic acids, and acyl quinic acid derivatives followed by flavonoids exemplified mainly by luteolin-C-glycosides and apigenin-C-glycosides. Quantification of the total phenolic and flavonoid contents in the total defatted methanolic extract confirmed its enrichment with phenolics and flavonoids equivalent to 138.61 ± 9.39 µg gallic acid/mg extract and 119.63 ± 4.62 µg rutin/mg extract, respectively. Moreover, the total defatted methanolic extract exhibited promising antioxidant activity confirmed through DPPH and ABTS assays with a 50% inhibitory concentration (IC50) value equivalent to 52.79 ± 2.16 µg/mL and 10.02 ± µg/mL, respectively. The inhibitory activity of acetylcholine esterase (AchE) was assessed using in-vitro Ellman's colorimetric assay, the total defatted methanolic extract, ethyl acetate, and n-butanol fractions exhibited IC50 values of 52.9, 15.1 and 108.8 µg/mL that they proved the significant inhibition of AchE activity. Conclusion The results obtained herein unraveled the potential use of the total methanolic extract of Vitex pubescens bark and its polar fractions as natural candidates for controlling Alzheimer's disease progression.